Role of the indoor environment in determining the severity of asthma. (1st August 1998) - Woodcock, A; Custovic, A
Abstract : Allergen exposure can confound the management of asthma. To understand the potential mechanisms by which allergens increase the steroid requirements in atopic asthmatics, we examined the effects of allergens on glucocorticoid receptor (GCR) binding affinity and glucocorticoid (GC) responsiveness of peripheral blood mononuclear cells (PBMC) from atopic asthmatics. A significant reduction (p < 0.001) in the GCR binding affinity (Kd) was observed in ragweed-allergic asthmatics during ragweed pollen season compared with PBMC obtained before and after ragweed season. In vitro effects of allergen on PBMC GCR Kd were also examined by incubating PBMC from atopic asthmatics with allergen (ragweed and cat) versus Candida albicans. GCR binding affinity was significantly reduced after incubation with ragweed (p < 0.001) or cat allergen (p < 0.001) compared with baseline or C. albicans stimulation. This effect was limited to atopic asthmatics in that in vitro cat allergen incubation for 48 h failed to significantly alter GCR binding affinity in nonasthmatic, atopic individuals. These allergen-induced reductions in GCR binding affinity also rendered the PBMC less sensitive to the inhibitory effects of hydrocortisone and dexamethasone on allergen-induced proliferation (p < 0.01). To test the hypothesis that allergen-induced alterations in GCR binding affinity were cytokine- induced, we examined the effects of interleukin-2 (IL-2) and IL-4 neutralization using anticytokine antibodies. Addition of both anti-IL- 2 and anti-IL-4 antibodies resulted in a significant (p < 0.001) inhibition of allergen-induced alterations in GCR binding affinity. Furthermore incubation with cat allergen induced significantly higher concentrations of IL-2 (p = 0.03) and IL-4 (p = 0.02) by PBMC from atopic as compared with nonatopic subjects. Our current observations suggest that allergen exposure may contribute to poor asthma control by reducing GCR binding affinity in mononuclear cells. This appears to be mediated through IL-2 and IL-4. These findings may have important implications for novel approaches to the treatment of poorly controlled asthma.